ROLE OF PRE-OPERATIVE WEIGHT, DEPRESSION, SELF-ESTEEM AND HISTORY OF SEXUAL ABUSE IN PREDICTING WEIGHT LOSS AFTER GASTRIC BYPASS - Qasim, Kashmala (My University, 2013)
Background: The objective of this thesis was to examine the role of psychosocial factors in weight loss success after bariatric surgery. It was proposed that a higher pre-operative body mass index (BMI), greater weight, depression, low self-esteem, and a childhood history of sexual abuse (CSA) would predict poor outcomes one year after Roux-en-y gastric bypass as evidenced by a BMI > 35 kg/m2 and a lower percent total weight loss (%TWL). Methods: We administered a battery of psychological screening tools, including the Beck Depression Inventory-II, the Rosenberg Self-Esteem Scale and a self-report measure assessing CSA, to 262 patients seeking bariatric surgery at St. Joseph's Healthcare Hamilton. Patients completed the questionnaires prior to surgery and again one year post-surgery. Results: On average patients (n = 79) achieved good weight loss outcomes (BMI = 32.8 kg/m2) at one-year follow-up. Through multiple regression analysis we found that pre-operative BMI accounted for a significant proportion of variance in postoperative BMI [R2 = .60, F(1, 77) = 114.4, p < .001]. Weight before surgery, however, did not predict %TWL after surgery. None of the psychosocial variables significantly predicted post-operative BMI or weight loss. These results are preliminary and are limited by the fact that participants did not present with clinically significant symptomatology and those with active psychopathology were excluded as suitable surgical candidates. Conclusion: These findings indicate that pre-operative BMI is a significant predictor of BMI one year after bariatric surgery, suggesting that more attention should be directed toward managing pre-operative BMI for heavier patients.
Keywords: Obesity; Bariatric Surgery; Roux en y Gastric Bypass; Psychosocial Factors; Body Mass Index; Depression; Nutritional and Metabolic Diseases; Psychiatric and Mental Health; Surgery; Nutritional and Metabolic Diseases